Differences in the Physical Workload of Technicians and Managers in the Maintenance and Repair Division - Innaha Ilma Wardaya; Ais Assana Athqia; Y. Denny A. Wahyudiono (Universitas Airlangga, 2022)
Introduction: PT. PAL Indonesia (Persero) is a state-owned company in the shipping industry. For running the production cycle, PT. PAL Indonesia (Persero) has several divisions. One of them is the Maintenance and Repair Division. This division involves workers with positions as technicians and managers who have different tasks and functions. These differences will result in unequal physical workloads. The purpose of this study is to analyze the differences in the physical workload of technicians and managers of the Maintenance and Repair Division of PT. PAL Indonesia (Persero). Methods: This study used an analytic observational method with a cross sectional design. The independent variable used in this research was the position of workers consisting of managers and technician staff. Meanwhile, the dependent variable was a physical workload. The research respondents were 24 technicians and 6 managers. Data were obtained through questionnaires and calorimeters to measure calorie needs. Results: The technicians were aged 20 - 33 years old (62.5%), and the managers were aged 48 - 61 years (83.3%). Technicians' nutritional status was categorized as normal, as many as 21 people and the nutritional status of managers was overweight, as many as 4 people. The physical workload of technicians was in the medium category, as many as 22 people and 5 managers had a moderate physical workload. Conclusion: There was no difference in the physical workload of technicians and managers of the Maintenance and Repair Division. This is because PT. PAL Indonesia (Persero) has implemented cooperation in job completion.